Social identity knowing yourself, leading others - Hannum, Kelly (Center for Creative Leadership, 2007)
"Today, leaders must bring together groups of people with very different histories, perspectives, values, and cultures. The people you lead are likely to be different from you and from each other in significant ways. Leaders today need an awareness of social identity, their own and that of others"--Resource description page
Includes bibliographical references (page 26). - Print version record
Keywords: Leadership; Executives -- Training of; BUSINESS & ECONOMICS; Development; Sustainable Development; Executives; Training of